The Impact of Stress Experienced by Students When Completing Thesis - Veronika Toru (JURNAL KESEHATAN PRIMER, 2019)
Background: The thesis preparation process raises internal stressors, external stressors and the impact of stress experienced by students in the thesis preparation process. This study aims to determine the impact of stress experienced by students when completing a Thesis at PSIK FK Undip. Method: This research is qualitative research with a phenomenological approach. The sample used was 6 students who were finishing their thesis in the Nursing Study Program of the Faculty of Medicine Undip, which was determined purposively. Data collection techniques with a Focus Group Discussion. Results: The problems experienced by students of the Nursing Study Program at the Faculty of Medicine Undip when completing the thesis were internal stressors and external stressors. The impact of stress experienced by students is the impact of stress that occurs on the physical, social and spiritual. Conclusion: The problem of stress experienced by students in the process of completing a thesis is the lack of student knowledge about research, the problem of lack of student coping strategies. Lack of available literature, poor relationship with supervisors and the effects of stress that is experiencing sleep patterns, dizziness/headaches, eating disorders and weight loss, irritability and concentration problems, interference with student communication with friends and others rarely pray and worship.